Employee Voice, Authentic Leadership, Innovative Work Behavior and Psychological Empowerment: A Multilevel Moderated Mediation - Noerchoidah Noerchoidah; Siti Istikhoroh; Dhyah Harjanti; Devi Rahnjen Wijayadne; Tony Susilo Wibowo (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: The dynamics of the tourism industry require companies to continue to innovate. As the company spearhead, employees need to be encouraged to continue to demonstrate innovative work behavior.  Purpose: This research explores the impact of authentic leadership and innovative work behavior, emphasizing the mediating role of employee voice and the moderating effect of psychological empowerment within the tourism industry in East Java. Design/methodology/approach: The type of research used is quantitative research with an explanatory approach, namely explaining the causal relationship between variables based on data collected through questionnaires. The study involved 217 respondents selected through a purposive sampling technique. The gathered data were analyzed using PLS-SEM.Findings/Result: The results showed that authentic leadership positively and significantly encourages employee voice, positively influencing innovative work behavior. In addition, employee voice can mediate authentic leadership and innovative work behavior. Psychological empowerment strengthens the influence of authentic leadership on innovative work behavior.Conclusion: Tourism industry management should promote openness and innovation among employees by positioning authentic leaders to foster an inclusive culture of innovation.Originality/value (State of the art): These findings offer valuable insights for tourism industry managers in East Java to enhance authentic leadership in fostering innovation. Keywords: authentic leadership, employee voice, innovative work behavior, psychological empowerment, tourism industry